Global reorganization of budding yeast chromosome conformation in different physiological conditions - Dultz, Elisa (J Cell Biol, 2016)
The organization of the genome is nonrandom and important for correct function. Specifically, the nuclear envelope plays a critical role in gene regulation. It generally constitutes a repressive environment, but several genes, including the GAL locus in budding yeast, are recruited to the nuclear periphery on activation. Here, we combine imaging and computational modeling to ask how the association of a single gene locus with the nuclear envelope influences the surrounding chromosome architecture. Systematic analysis of an entire yeast chromosome establishes that peripheral recruitment of the GAL locus is part of a large-scale rearrangement that shifts many chromosomal regions closer to the nuclear envelope. This process is likely caused by the presence of several independent anchoring points. To identify novel factors required for peripheral anchoring, we performed a genome-wide screen and demonstrated that the histone acetyltransferase SAGA and the activity of histone deacetylases are needed for this extensive gene recruitment to the nuclear periphery.